A Novel Embedded System on Cold Box Design for The Cold Chain - Mucahid Mustafa Sarıtas; Murat Koklu; Ilker Ali OZKAN (International Journal of Applied Methods in Electronics and Computers, 2017)
The “cold chain” enables to remain safely the vaccines and medicines at the recommended temperature ranges during their transportation and storage period from the production site to the end user. The cold chain system is very important because of that vaccines and medicines lose their effectiveness when they exposed to a temperature above or below the limited ranges. There is no benefit of the vaccination also, if the vaccines and medicines used were ineffective; on the contrary, the vaccine can injure the applied organism. In this study, a kit based on “Arduino” was designed to ensure the continuity of the cold chain effectiveness. With this study intended was a new system designed, which enables a real time temperature and humidity control of the cold chain system in the transport ambient conditions so that it will alert when the cold chain system should have a malfunction. On the other hand, the experimental results obtained were compared which were sensitively measured with a laser thermometer capable for remote measuring. There was no difference between the results obtained and the values measured by the laser thermometer. Additionally, performance analyses of the system at the different temperatures have revealed that it is capable to stabilize the temperature value successfully.